2003
DOI: 10.1073/pnas.1031851100
|View full text |Cite
|
Sign up to set email alerts
|

Inducible expression of keratinocyte growth factor (KGF) in mice inhibits lung epithelial cell death induced by hyperoxia

Abstract: Oxidant-induced injury to the lung is associated with extensive damage to the lung epithelium. Instillation of keratinocyte growth factor (KGF) in the lungs of animals protects animals from oxidantinduced injury but the mechanism of protection is not well understood. An inherent problem in studying KGF function in vivo has been that constitutive overexpression of KGF in the lung causes embryonic lethality with extensive pulmonary malformation. Here we report the development of a stringently regulated, tetracyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
107
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 63 publications
(94 reference statements)
8
107
0
1
Order By: Relevance
“…[9][10][11][12][25][26][27][28][29][30][31] With the availability of sophisticated computer-controlled modification systems for clinical radiotherapy dose distribution by modern linear accelerators including intensity-modulated radiation therapy, 1,2,7 many physical barriers to dose optimization in complex tumor volumes have been overcome. Unfortunately, effective high dose delivery to complex tumor volumes in the thoracic cavity, which has been developed for patients with lung cancer, esophagus cancer, and other thoracic malignancies, has necessitated often large lung transit volumes and associated toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][25][26][27][28][29][30][31] With the availability of sophisticated computer-controlled modification systems for clinical radiotherapy dose distribution by modern linear accelerators including intensity-modulated radiation therapy, 1,2,7 many physical barriers to dose optimization in complex tumor volumes have been overcome. Unfortunately, effective high dose delivery to complex tumor volumes in the thoracic cavity, which has been developed for patients with lung cancer, esophagus cancer, and other thoracic malignancies, has necessitated often large lung transit volumes and associated toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologic interventions and biologic response modifiers have recently been focused on pulmonary radiation protection. Intravenous or systemic delivery of compounds such as WR2721 (Amifostine), [9][10][11][26][27][28][29]32 colony stimulating factors, 31 or other antioxidant molecules 30,33,34 has the potential problem of distribution to tumor vasculature within the target volume. 27,29 Simultaneous tumor and normal tissue radiation protection would not alter the therapeutic ratio or shift to a desirable effect of normal tissue radiation protection.…”
Section: Discussionmentioning
confidence: 99%
“…5. reduces alveolar capillary permeability, pulmonary oedema and improves survival in animal models of ALI ). 6. has anti-apoptotic effects via the Akt pathway (Ray P, Devaux Y et al 2003) Recombinant human KGF (palifermin) is a 140 amino acid protein with a molecular weight of 16.3 kilodaltons (kDa) and differs from endogenous KGF in that the first 23 Nterminal amino acid residues have been to deleted to improve protein stability. Palifermin is produced by recombinant DNA technology in Escherichia coli (Blijlevens and Sonis 2007).…”
Section: Evidence For Keratinocyte Growth Factor (Kgf) As a Novel Thementioning
confidence: 99%
“…The KGFR is expressed only in epithelial cells and it plays critical roles in the proliferation, migration, and morphogenesis of epithelial cells (Ulich et al, 1994;Wilson et al, 1994;Post et al, 1996;Buckley et al, 1997). The KGFR also plays important roles in skin wound healing and lung epithelial cell survival during injury (Werner et al, 1994;Panos et al, 1995;Yi et al, 1996;Barazzone et al, 1999;Das and Olsen, 2001;Ray et al, 2003). The KGFR is activated by FGF-1, FGF-3, KGF/FGF-7, and FGF-10, whereas FGFR2 is mainly activated by FGF-2/bFGF (Bottaro et al, 1990;Miki et al, 1991Miki et al, , 1992Orr-Urtreger et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…RSKs are activated in response to several growth factors and mitogens including EGF (Zhao et al, 1996; Sassone-Corsi et al, 1999), insulin, and IGF-I (Alessi et al, 1995;Lazar et al, 1995). The activated RSKs phosphorylate a number of proteins containing the consensus sequences (R/ L)xRxxS and are involved in a wide range of cellular activities (Frodin and Gammeltoft, 1999).Using a lung-specific inducible transgenic system, we recently showed that KGF overexpression in the lung inhibits lung epithelial cell death (Ray et al, 2003). Our studies showed that KGF-mediated epithelial cell survival from oxidative stress involves the prosurvival Akt pathway (Ray et al, 2003).…”
mentioning
confidence: 99%